2003
DOI: 10.1002/pssc.200306253
|View full text |Cite
|
Sign up to set email alerts
|

Defect topography on GaAs wafers by microwave‐detected photo‐induced current transient spectroscopy

Abstract: PACS 71.55. Eq, 72.40.+w Photo-generated charge carriers can be detected by microwave absorption. This enables non-destructive measurements of photoconductivity with a spatial resolution depending on the spot size of the light source. In addition, the photoconductivity can be measured as a function of time during light on and off with high time resolution. The resulting photoconductivity transients contain information about defect parameters like conventional methods such as deep level transient spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Moreover, it is shown that the method of microwave detected photoconductivity (MDP), which was successfully applied to investigate the homogeneity of GaAs wafers [10][11][12][13][14][15][16], works as successfully for InP wafers. The nature of the contrast causing defects is not yet known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it is shown that the method of microwave detected photoconductivity (MDP), which was successfully applied to investigate the homogeneity of GaAs wafers [10][11][12][13][14][15][16], works as successfully for InP wafers. The nature of the contrast causing defects is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental setup for the microwave detected photocurrent measurements MDP and MD-PICTS was already described elsewhere [10][11][12][13]. Through band-to-band excitation (hν ≥ 1.3eV) excess carriers are generated, which are detected via high sensitivity microwave absorption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave detected photo induced current transient spectroscopy (MD-PICTS) is a well-known tool for the contact-less and non-destructive investigation of electrical properties of defects in semiconductors [1][2][3]. Especially in semi-insulating GaAs (SI-GaAs) positive and negative PICTS peaks, which are mostly attributed to the EL2 defect, can be observed at temperatures above &350 K, whereas the exact peak maximum temperature depends on the details of the applied PICTS data evaluation.…”
Section: Introductionmentioning
confidence: 99%